Experimentelle und numerische Analyse des Körperschallübertragungsverhaltens von Aggregatelagerelementen im akustisch relevanten Frequenzbereich - Watzl, Sebastian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
The structure-borne sound transmission properties of hydraulic and conventional engine mounts is analyzed experimentally and numerically in a acoustically relevant frequency range. In order to do so, first of all a test bench environment for analyzing the dynamic sound transmission properties is presented. In subsequent steps the main influence parameters on the transmission properties are determined experimentally and numerically.